2012
DOI: 10.1074/jbc.m112.342873
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Expression of Inter-α-inhibitor (IαI) Family Proteins and Tumor Necrosis Factor-stimulated Gene-6 (TSG-6) by Human Amniotic Membrane Epithelial and Stromal Cells Supporting Formation of the Heavy Chain-Hyaluronan (HC-HA) Complex

Abstract: Background: The heavy chain-hyaluronan (HC-HA) complex from amniotic membrane (AM) has anti-inflammatory, anti-scarring, and anti-angiogenic actions.Results: AM epithelial and stromal cells constitutively expressed IαI and TSG-6 supporting the production of HC-HA.Conclusion: AM is an extrahepatic tissue constitutively producing its own IαI and HC-HA complex.Significance: HC-HA endogenously produced by AM may play an important protective role during fetal development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
73
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 60 publications
(80 citation statements)
references
References 80 publications
(123 reference statements)
6
73
1
Order By: Relevance
“…HC1 and PTX3, but Not HC2, Bikunin, and TSG-6, Are Present in HC-HA-We previously reported that HC-HA purified from human AM contains HC1 but not HC2 of I␣I (42). To further confirm this, HC-HA purified through two sequential runs of ultracentrifugation in CsCl, 4 M guanidine HCl was subjected to a mild NaOH (0.05 N) treatment to cleave the ester bond between HC and HA (47) or digestion with HAase to release HC.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…HC1 and PTX3, but Not HC2, Bikunin, and TSG-6, Are Present in HC-HA-We previously reported that HC-HA purified from human AM contains HC1 but not HC2 of I␣I (42). To further confirm this, HC-HA purified through two sequential runs of ultracentrifugation in CsCl, 4 M guanidine HCl was subjected to a mild NaOH (0.05 N) treatment to cleave the ester bond between HC and HA (47) or digestion with HAase to release HC.…”
Section: Resultsmentioning
confidence: 88%
“…This finding suggests that SHAP-HA has an inhibitory role in the development of airway hyper-responsiveness and allergic airway inflammation (66). Although both SHAP-HA and HC-HA purified from human AM are similar complexes, characterized by high molecular mass HA covalently linked to HC (42,43,64), there are important differences. In adult cells, SHAP-HA contains both HC1 and HC2 from serum I␣I (derived from the liver) (64).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…I␣I has been described to be necessary for the cumulus formation of the ovary (31) and to play an important role in tissue repair (34,42,43). Moreover, an isoform of I␣I has been reported to be produced by the amniotic membrane, and the hyaluronan-HC (HC⅐HA) complex is present in amniotic fluid, giving evidence of TSG-6 mediated transfer of HCs to hyaluronan in amniotic tissue (32,44). These data suggest that the HCs play a role during embryonic development and may also be important for ES cell maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Sanggaard et al suggests that HC2 is necessary for the TSG-6-mediated transfer to take place, possibly explaining both the inability of HC1 alone to induce TEAD family and the need for higher concentrations of HC2 to induce a robust effect on TEAD activity (45). Interestingly, Zhang et al studied the presence of HCs coupled to hyaluronan in amniotic membrane, and found that whereas the amniotic membrane produces HC1, HC2, and HC3, only HC1⅐HA complex was found in physiological amniotic membrane extracts (44), which could account for the anti-inflammatory, anti-scarring, and anti-angiogenic effects that this particular HCŸHA complex yields (46).…”
Section: Discussionmentioning
confidence: 99%